Invasive Plant Species in Mangrove Wetlands: Patterns of Spread and Ecological Threats (Indian Journal of Advanced Botany (IJAB), 2025)
Biological invasions pose a serious threat to natural ecosystems. Mangroves are vulnerable to invasion by salt-tolerant aquatic and terrestrial plants, such as epiphytes, despite their extremely saline and intertidal habitat. The present study examines the invasion rates and assesses the ecological impacts of invasive plant species on the mangrove flora of Kannur District, Kerala. Extensive field visits were conducted in the selected study stations to analyse plant species using the line transect method. A total of 21 plant species, including 7 true mangroves and eight mangrove associates, were recorded from the study areas. Out of the identified plant species, 11 are invasive, belonging to 5 families and 11 genera. The highest invasion rate was observed in Ipomoea cairica (1.203) at site-2, followed by Volkameria inermis (4.404×10-1 ). The competition between invasive plants and native species for light, nutrients, and space impacts the growth, development, and diversity of mangroves. Well-framed policies and effective management strategies are vital to curb invasive plant spread and safeguard the long-term conservation of mangrove ecosystems.